Functional Characterization and Structural Modelling of Peptidoglycan Degrading β-N-acetyl-glucosaminidase from a Dental Isolate of Serratia marcescens - Rathee, Aditi; Panwar, Anil; Kumari, Seema; Chhibber, Sanjay; Kumar, Ashok (Combinatorial Chemistry & High Throughput Screening, 2021)
Introduction: Enzymatic degradation of peptidoglycan, a structural cell wall component of Gram-positive bacteria, has attracted considerable attention being a specific target for many known antibiotics. Methods: Peptidoglycan hydrolases are involved in bacterial lysis through peptidoglycan degradation. β-N-acetyl-glucosaminidase, a peptidoglycan hydrolase, acts on O-glycosidic bonds formed by N-acetylglucosamine and N-acetyl muramic acid residues of peptidoglycan. Aim of present study was to study the action of β -N-acetylglucosaminidase, on methicillin-resistant Staphylococcus aureus (MRSA) and other Gram-negative bacteria. Results: We investigated its dynamic behaviour using molecular dynamics simulation and observed that serine and alanine residues are involved in catalytic reaction in addition to aspartic acid, histidine, lysine and arginine residues. When simulated in its bound state, the RMSD values were found lesser than crystal form in the time stamp of 1000 picoseconds revealing its stability. Structure remained stably folded over 1000 picoseconds without undergoing any major change further confirming the stability of complex. Conclusion: It can be concluded that enzymes belonging to this category can serve as a tool in eradicating Gram-positive pathogens and associated infections.
Keywords: docking